PENGARUH AUDITOR SIZE, AUDITOR TENURE DAN KEPEMILIKAN INSTITUSIONALTERHADAP BIAYA MODAL EKUITAS - Meilisa, Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to examine the effect of the auditor size, auditor tenure, and institutional ownership against the cost of equity capital. The research sample is selected by purposive sampling method, which is manufacturing companies listed on the Indonesian Stock Exchange from 2016 to 2018 period. From the sample selection process, obtained 95 companies during the past 3 years or as many as 147 data. Analysis of data using multiple regression analysis using the IBM SPSS Statistics 23 program. The results showed that auditor tenure affect negatively significant to cost of equity capital, while auditor size and institutional ownership have a non-significant affect on cost of equity capital.